Individual differences in nonnative lexical tone perception: Effects of tone language repertoire and musical experience - Toh, Xin Ru; Lau, Fun; Wong, Francis C. K. (Frontiers in Psychology, 2022)
This study sought to understand the effects of tone language repertoire and musical experience on nonnative lexical tone perception and production. Thirty-one participants completed a tone discrimination task, an imitation task, and a musical abilities task. Results showed that a larger tone language repertoire and musical experience both enhanced tone discrimination performance. However, the effects were not additive, as musical experience was associated with tone discrimination performance for single-tone language speakers, but such association was not seen for dual-tone language speakers. Furthermore, among single-tone language speakers, but not among dual-tone language speakers, musical experience and musical aptitude positively correlated with tone discrimination accuracy. It is thus concluded that individuals with varying extents of tone language experience may adopt different strategies when performing tone discrimination tasks; single-tone language speakers may draw on their musical expertise while dual-tone language speakers may rely on their extensive tone language experience instead.